Kudeta Militer Niger 2023: Analisis Latar Belakang - Jonathan Stanley Federico Purnomo; Aryanta Nugraha (Journal Pena Wimaya, 2026)
This study analyzes the background of the military coup in Niger on July 26, 2023, which overthrew President Mohamed Bazoum. The fifth coup since the country’s independence occurred amid a multidimensional crisis that had weakened the legitimacy of the civilian government. This research aims to explain the causal factors of the coup using Eric A. Nordlinger’s analytical framework, which distinguishes between structural (long-term) factors and contextual (immediate trigger) factors. The method employed is qualitative descriptive, with data collected through library research. The findings reveal that the structural factors include Bazoum’s delegitimization in the socio-political domain (legacy of Issoufou’s patronage system and his minority Arab ethnic identity), the security domain (deteriorating terrorism threat in the Sahel and pro-Western foreign policy), and the economic domain (chronic poverty, inequality in natural resource management, and dependence on foreign aid). Meanwhile, the contextual factors consist of the accumulation of military dissatisfaction across these three domains, which was then directly triggered by the dismissal of General Salifou Modi from his position as Chief of Staff of the Army (April 1, 2023) and the planned dismissal of General Abdourahmane Tchiani from his position as Head of the Presidential Guard (July 24, 2023). This study concludes that the 2023 coup was the result of an interaction between long-term structural delegitimization and short-term contextual triggers, which together enabled military intervention. Keywords: 2023 Niger coup; structural factors; contextual factors; Mohamed Bazoum; Abdourahmane Tchiani